Design for Product Care—Development of Design Strategies and a Toolkit for Sustainable Consumer Behaviour. Issue 2 (28th April 2021) - Ackermann, Laura; Tuimaka, Mahana; Pohlmeyer, Anna E.; Mugge, Ruth
No abstract available